Dermatology life quality index in vitiligo patients: A systematic review and meta-analysis of observational studies - Reza Ghanei Gheshlagh; Kamel Abdi; Mojtaba Jafari; Pegah Dalvand; Sholeh Saedmocheshi; Asra Nassehi (Tehran University of Medical Sciences, 2024)
Background & Aim: Vitiligo is a chronic and unpredictable condition. The absence of effective treatments, coupled with fears of rejection and stigma, can adversely affect patients' coping abilities and their social and psychological adjustment. This study aimed to assess the overall quality of life score of vitiligo patients using DLQI to evaluate the disease's impact on their quality of life. Methods & Materials: This meta-analysis adhered to PRISMA 2020 guidelines and thoroughly searched the PubMed, EMBASE, Web of Science/ISI, and Scopus databases from their inception to January 2023. All observational studies reporting the quality of life score based on the DLQI were included in the analysis. Heterogeneity among the studies was assessed using the I2 index and Cochrane's Q-statistic. Data were analyzed using the random effects model using STATA software version 12. Results: Our analysis included a total of 58 studies involving 9277 individuals. The pooled DLQI score was 8.07 (95% CI: 7.22-8.91). The lowest and highest scores were observed in Europe (5.52, 95% CI: 4.18-6.87) and Africa (10.95, 95% CI: 7.77-14.15), respectively. The DLQI score was 7.17 (95% CI: 6.04-8.31) in men and 8.63 (95% CI: 7.44-9.82) in women. No significant correlation was found between the DLQI score and the publication year of the articles (p=0.219), patients' age (p=0.119), and disease duration (p=0.203). Conclusion: Vitiligo moderately impacts patients' quality of life. Therefore, it seems necessary to provide psychological and social training for these patients.